2021
DOI: 10.1007/s00402-021-04113-6
|View full text |Cite
|
Sign up to set email alerts
|

Vancouver B and C periprosthetic fractures around the cemented Exeter Stem: sex is associate with fracture pattern

Abstract: Introduction The aim of this study was to identify factors associated with the level of periprosthetic fracture involving a cemented polished tapered stem: Vancouver B or Vancouver C. Methods A retrospective cohort study of 181 unilateral periprosthetic fractures involving Exeter stems was assessed by three observers (mean age 78.5, range 39–103; mean BMI 27.1, 17–39; 97 (54%) male). Patient demographics, deprivation scores, BMI and time since primary pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 25 publications
(49 reference statements)
1
5
0
Order By: Relevance
“…These findings support previous studies; periprosthetic proximal femoral fractures, especially Vancouver Type C fractures, display typical fragility fracture characteristics, and this type is associated with female sex and high mortality [5, 17]. Moreover, Powell-Bowns et al [25] showed that the mortality of patients with Vancouver Type C fractures was higher than those with Vancouver Type B fractures, which also agrees with our study findings. Interestingly, previous studies have shown that male patients with periprosthetic proximal fracture have a higher risk of death than women do [10, 17].…”
Section: Discussionsupporting
confidence: 93%
“…These findings support previous studies; periprosthetic proximal femoral fractures, especially Vancouver Type C fractures, display typical fragility fracture characteristics, and this type is associated with female sex and high mortality [5, 17]. Moreover, Powell-Bowns et al [25] showed that the mortality of patients with Vancouver Type C fractures was higher than those with Vancouver Type B fractures, which also agrees with our study findings. Interestingly, previous studies have shown that male patients with periprosthetic proximal fracture have a higher risk of death than women do [10, 17].…”
Section: Discussionsupporting
confidence: 93%
“…20 We also observed a variation in sex distribution dependent upon fracture type which was similar to other studies. 21,22 The NJR reports that 60% (total hip arthroplasty (THA)) and 56% (total knee arthroplasty) of primary arthroplasties are performed in females. This contrasts with a female proportion of 58% and 84% for hip and knee femoral PPFs, respectively, suggesting that sex is variably associated with the risk of a femoral PPFs dependent upon the joint involved.…”
Section: Discussionmentioning
confidence: 99%
“…17 Patients with a periprosthetic fracture around the knee or those with type C or D interprosthetic fractures appear to be the most frail and elderly. 2,17,18 These patients are particularly at risk of morbidity from blood loss and prolonged surgery. It is not surprising therefore that these fractures are associated with mortality rates of 21% one year postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…17 Patients with a periprosthetic fracture around the knee or those with type C or D interprosthetic fractures appear to be the most frail and elderly. 2,17,18 These patients are particularly at risk of morbidity from blood The medial fat stripe. The purple line represents the proximal extent of a standard medial patellar approach.…”
Section: Discussionmentioning
confidence: 99%